Legal Effects of Personal Execution in the Administrative Contract - Khudair, Mahmoud Khalil Khudair (Journal of Legal Sciences, 2022)
The contracts management style, a distinctive and important practice management through active administratively closed facility in aiming to ensure the continuity of the Facility regularly and Adtarad where walk in the light of this style approach satisfaction and understanding through the conclusion of the contract administrative and through an agreement with one of the natural or legal persons n this style resorted to by the administration if it does not Asafha administrative decision in the exercise of its activity, or if he believes that the style of management contracts better able to achieve its goals.There is administrative contracts general principle expressed the commitment of the contractor with the administration, implementation of the personal contract this principle, which is based on the mainstay, but an idea account Profile The Contractor shall comply with the administration to implement its obligations personally and himself is to have a general rule, the right to transfer them to others or contracted subcontractors the contractor a second so that the figure contracted to be subject to consideration by the administration, both at the conclusion of the contract or when implemented as the administration must take into account the availability of certain considerations, or in other words, that the administration as a party to the contract administrative must - when choosing a contractor - that take into account In this choice the availability of a range of essential qualities in the person you want to sign him, so as to ensure the implementation of the contract properly and in a manner in the public interest to the fullest, which believes in the progress of attachment underlying regularly permanent, and so the idea of mind Profile is one of the basic ideas both with regard to the selection of the contractor or the execution of the contract as to the selection of the contractor, the administration has the discretion to refrain from contracting with someone to Atrtadhah even handpicked committee to decide, either with respect to implementation of the administrative judiciary - in most of the countries that take justice system double - stressed It's the basic principles that the implementation of the contractor himself, due to the close connection with the contract administrative annex Valtzamat year contracted with the administration, personal commitments and can not be him that solves the other Raises the question many questions, mainly over the relationship between the mind and personal contract execution and administrative What are the results of principle in the implementation of the contract administrative Is it permissible to waive the non-implementation of the contract and what is the impact of circumstances that may arise during the implementation phase of the Association of Streptococcus commute the contractor and the bankrupt or insolvent.